Fashion and Architecture in the Art of Making Aesthetic Artworks - Ardiani, Yanita Mila (Institut Seni Indonesia Denpasar, 2025)
Various multidisciplinary sciences combine to provide architectural inspiration. The interrelationship between fashion and architecture serves as a catalyst for architects' creative output. Fashion can inspire architectural forms and architectural forms can inspire the latest fashion forms. This paper discusses about other things can be discovered from this experiment in discovering aesthetic forms. The method used is collecting precedent studies and literary studies related to these matters. The outcomes of these form experiments and discussions inspire students to create an architectural piece that combines fashion and architecture for aesthetic appeal. The composition of a work of architecture shares similarities with that of fashion.